Study of Barium Adsorption from Aqueous Solutions Using Copper Ferrite and Copper Ferrite/rGO Magnetic Adsorbents - B. Carmel Jeeva Mary; J. Judith Vijaya; M. Bououdina; L. Khezami; A. Modwi; M. Ismail; Stefano Bellucci (Adsorption Science & Technology)
The development of advanced materials for the removal of heavy metal ions is a never-ending quest of environmental remediation. In this study, a facile and cost-effective approach was employed to synthesize copper ferrite (CF) and copper ferrite/reduced graphene oxide (CG) by microwave assisted combustion method for potential removal of barium ions from aqueous medium. The physiochemical characterizations indicated the formation of magnetic nanocomposite with an average crystallite size of CF and CG is 32.4 and 30.3 nm and with specific surface area of 0.66 and 5.74 m2/g. The magnetic results possess multidomain microstructures with saturation magnetization of 37.11 and 33.84 emu/g for CF and CG. The adsorption studies prove that upon addition of rGO on the spherical spinel ferrite, the adsorption performance was greatly improved for CG nanocomposite when compared with the bare CF nanoparticles. The proposed magnetic adsorbent demonstrated a relatively high Ba2+ adsorption capacity of 161.6 mg·g-1 for CG nanocomposite when compared to 86.6 mg·g-1 for CF nanoparticles under optimum conditions (pH=7;T=25°C). The pseudo-first-order (PFO), pseudo-second-order (PSO), and Elovich models were fitted to the kinetic data, the yielded R2 value of 0.9993 (PSO) for CF and 0.9994 (PSO) for CG which is greater than the other two models, which signify that the adsorption process is chemisorption. Thermodynamic studies show that barium adsorption using CF and CG adsorbents is endothermic. The as-fabricated CuFe2O4/rGO nanocomposite represents a propitious candidate for the removal of heavy metal ions from aqueous solutions.